Assessing a laboratory test on food preferences of the melon fruit fly, Bactrocera cucurbitae (Diptera: Tephritidae) - Nor Aminah Azizol Azeli,; Salmah Mohamed,; Nur Syahida Wajdah Saidi,; Norhayati Ngah,; Nur Athiqah Md Yusof,; Nur Azura Adam, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Controlling the melon fruit fly, Batrocera cucurbitae (Diptera: Tephritidae) can be achieved by employing food bait trapping techniques that could reduce reliance on insecticides. However, the success of this method depends on several factors which include the sweetness and nutritional value of the food, as well as other population-affecting factors. As a result, performing laboratory studies becomes crucial in order to observe the behaviour and tendencies of the melon fruit fly towards their dietary choices. Therefore, the objective of this study was to evaluate the food preferences of melon fruit flies in the laboratory before applying food in baited traps for field studies. The study employed a choice and no choice experiment, presenting four types of foods: Brewer's yeast, banana, cucumber, and Melon Manis Terengganu (MMT). Each experiment involved releasing a four-day-old adult female of B. cucurbitae into a rearing cage containing the four foods for choice and each food (individually) for no-choice experiment. The fly's foraging behaviour was observed and recorded for a duration of two hours with five replications. The results indicated significant differences (P<0.05) in the duration of food consumption by the flies when exposed to different host foods for both experiments. Notably, the yeast recorded the significantly longest duration of food consumption with 19.29±3.73 minutes for choice experiment and 21.44±8.22 minutes for no choice experiment, compared with other food hosts. However, no significant differences (P>0.05) were observed in the number of food visits, duration of food visits, and number of consumptions across all the food hosts. These findings highlight the importance of using yeast as one of the food baits in the management of melon fruit flies. Its incorporation enhances pest control methods, contributing to a more efficient and environmentally friendly approach to managing this pest.